Bilingual exposure might enhance L1 development in Cantonese–English bilingual autistic children: Evidence from the production of focus - Ge, Haoyan; Lee, Albert Kwing Lok; Yuen, Hoi Kwan; Liu, Fang; Yip, Virginia (Autism : the international journal of research and practice, 2024)
This study investigated bilingualism effects on the production of focus in 5- to 9-year-old Cantonese–English bilingual autistic children’s L1 Cantonese, compared to their monolingual autistic peers as well as monolingual and bilingual typically developing children matched in nonverbal IQ, working memory, receptive vocabulary and maternal education. The results from an elicitation task showed that monolingual autistic children had significantly lower accuracy than typically developing children in producing focus in subject and object positions. Bilingual autistic children in general performed similarly to monolingual autistic children but outperformed their monolingual autistic peers in the production of object focus with a significantly higher accuracy. The total amount of English exposure did not relate to the accuracy of focus production in autistic and typically developing children. Our results also revealed autistic children’s tendency to make use of less prosodic means to produce focus. The overall findings indicate that bilingual exposure has no detrimental effect on the language skills of autistic children but might enhance the production of focus in bilingual autistic children’s L1 Cantonese. Lay abstract It is commonly believed among professionals and parents that exposure to two languages imposes an additional burden on children with autism spectrum disorder. However, there is a lack of empirical evidence to support or reject this belief. With the prevalence of autism and an increasing number of children growing up bilingual, it is urgent to understand how bilingual exposure interacts with autism. Bilingual autistic children from Hong Kong, with Cantonese as their first language and English as their second language, took part in the study. We used a production game to test how bilingual autistic children use different levels of linguistic knowledge to produce contrastive information in real conversations, compared to their monolingual autistic peers and typically developing children matched in language abilities, nonverbal IQ, working memory and maternal education. We found that bilingual autistic children performed as good as typically developing children in general, and they even performed better than monolingual autistic children. Our findings suggest a bilingual advantage in autistic children in conveying constative information in sentences. We thus encourage parents to engage their children in rich bilingual environments. Clinicians, educators and other professionals may also consider adding bilingual aspects in training programmes to support families raising bilingual autistic children.